Pengaruh Biaya Periklanan Dan Biaya Promosi Penjualan Terhadap Volume Penjualan Pada Pt. Agung Automall Soetomo Pekanbaru - Restuti, Sri; Rahayu, Deny Danar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to measure the effect of the advertising fee which consists of; the cost of print advertising, radio broadcasting costs, the cost of brochures / booklets and sales promotion which consists of; the cost of monthly exhibitions as well as a raffle coupon to sales volume PT. Agung Automall located Soetomo streets of Pekanbaru. In this study consists of five independent variables consisting of print ads (X1), radio (X2), brochures and booklets (X3), the cost of monthly exhibitions (X4), the cost of lottery tickets (X5) and the dependent variable sales volume (Y ). This study uses data analysis using multiple linear regression (multiple regression) with SPSS (Statistic Services For Product and Solution) Version 17.0 These results indicate that the advertising and sales promotion variables simultaneously (test f) significant positive effect on the volume of sales at PT. Agung Automall Soetomo Pekanbaru, while (t test) in partial print ads, radio, brochures / booklets, monthly exhibitions as well as lottery tickets, just print ads and promotional monthly significant effect on the volume of sales at PT. Agung Automall Soetomo Pekanbaru. Adusjted (R2) square of the model influence the cost of advertising and sales promotion expenses to sales volume in PT. Agung Automall Soetomo Pekanbaru by sixtyone point eight percent. While the remaining thirty-eight point two percent is influenced by other variables not examined in this study.Keywords: Advertising Costs, Costs of Sales Promotion, Sales Volume